Association between loop diuretic dose changes and outcomes in chronic heart failure: observations from the ESC‐EORP Heart Failure Long‐Term Registry. (1st April 2020) - Kapelios, Chris J.; Laroche, Cécile; Crespo‐Leiro, Maria G.; Anker, Stefan D.; Coats, Andrew J.S.; Díaz‐Molina, Beatria; Filippatos, Gerasimos; Lainscak, Mitja; Maggioni, Aldo P.; McDonagh, Theresa; Mebazaa, Alexandre; Metra, Marco; et al.
Abstract: Aims: Guidelines recommend down‐titration of loop diuretics (LD) once euvolaemia is achieved. In outpatients with heart failure (HF), we investigated LD dose changes in daily cardiology practice, agreement with guideline recommendations, predictors of successful LD down‐titration and association between dose changes and outcomes. Methods and results: We included 8130 HF patients from the ESC‐EORP Heart Failure Long‐Term Registry. Among patients who had dose decreased, successful decrease was defined as the decrease not followed by death, HF hospitalization, New York Heart Association class deterioration, or subsequent increase in LD dose. Mean age was 66 ± 13 years, 71% men, 62% HF with reduced ejection fraction, 19% HF with mid‐range ejection fraction, 19% HF with preserved ejection fraction. Median [interquartile range (IQR)] LD dose was 40 (25–80) mg. LD dose was increased in 16%, decreased in 8.3% and unchanged in 76%. Median (IQR) follow‐up was 372 (363–419) days. Diuretic dose increase (vs. no change) was associated with HF death [hazard ratio (HR) 1.53, 95% confidence interval (CI) 1.12–2.08; P = 0.008] and nominally with cardiovascular death (HR 1.25, 95% CI 0.96–1.63; P = 0.103). Decrease of diuretic dose (vs. no change) was associated with nominally lower HF (HR 0.59, 95% CI 0.33–1.07; P = 0.083) and cardiovascular mortality (HR 0.62, 95% CI 0.38–1.00; P = 0.052). Among patients who had LD dose decreased, systolic blood pressure [odds ratio (OR) 1.11 per 10 mmHg increase, 95% CI 1.01–1.22; P = 0.032], and absence of (i) sleep apnoea (OR 0.24, 95% CI 0.09–0.69; P = 0.008), (ii) peripheral congestion (OR 0.48, 95% CI 0.29–0.80; P = 0.005), and (iii) moderate/severe mitral regurgitation (OR 0.57, 95% CI 0.37–0.87; P = 0.008) were independently associated with successful decrease. Conclusion: Diuretic dose was unchanged in 76% and decreased in 8.3% of outpatients with chronic HF. LD dose increase was associated with worse outcomes, while the LD dose decrease group showed a trend for better outcomes compared with the no‐change group. Higher systolic blood pressure, and absence of (i) sleep apnoea, (ii) peripheral congestion, and (iii) moderate/severe mitral regurgitation were independently associated with successful dose decrease.